Bullous pemphigoid and morphea: Coexistence or an incidental association - Seema Rani; Sweta Singh; Arvind Ahuja (Indian Journal of Allergy Asthma and Immunology)
Morphea is considered an autoimmune disease because of reported autoantibody and autoimmune disease associations and is characterized by varying degrees of sclerosis, fibrosis, and atrophy in the skin and subcutaneous tissues and may involve muscle, bone, and brain. Plaque morphea is the most common subtype occurring in adults followed by generalized and linear. The various inciting factors for morphea are trauma, radiation, drugs, and vaccination. The occurrence of bullous lesions in localized or systemic scleroderma is rare. Bullous pemphigoid (BP) is the most common autoimmune blistering skin disorder, in which autoantibodies target two hemidesmosomal components BP180 (Collagen XVII) and/or BP230. Although the etiology of BP remains uncertain, various diseases or treatments may be associated with the onset of BP, including neurological disorders, ultraviolet therapies, and drugs. In this report, we describe an old diabetic patient with a history of plaque morphea who developed BP while in remission from treatment.